Converting conflicts in preschool - Beaty, Janice J. (Fort Worth, TX : Harcourt Brace College, 1995)
It's high time! It's mine! (Possession disputes). Look at me! (Attention getting). Who's in charge? (Power struggles)...
Keywords: Education; Preschool; Classroom management; Conflict management; Education, Preschool